Impact Of Edge Effect On Diversity And Diet Of Insectivorous Bats In Penang Island - Mohamed, Mansour Saad Abulqasim (2021)
Habitat loss in Penang Island is recently rising due to the changes in the natural vegetation cover resulting from the agriculture and urbanization. The effect of edge formation has not been studied on bat population in Penang Island. The purpose of this thesis is to fill multiple research gaps related to the insectivorous bats in the forest edges of Penang Island, thereby increasing scientific understanding of how edge effects impact Paleotropical bats. First, the impact of edge effects on an insectivorous bat community composition was studied. Mist nets and harp traps were employed from January through December 2019 to record species abundance, richness and diversity in an assemblage of bats in two sites of a forest edge. The overall Shannon estimate of diversity was relatively not high (H' = 1.38), but the 13 discovered species, 15–19 estimated species and a higher capture rate (4.18/ trap-night) indicated that edge effects probably influence the diversity in Paleotropical bat assemblages. There was no difference in species diversity between dark and light sites of the edge (11 species each), but some species individually captured in one site more than the other. Second, diets of common insectivorous bat species in the studied area (Hipposideros armiger, Hipposideros kunzi, Rhinolophus affinis, Rhinolophus lepidus, Rhinolophus pusillus and Rhinolophus stheno) were examined using the fecal analysis.